2007
DOI: 10.1093/pcp/pcl041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a WRKY Protein as a Transcriptional Regulator of Benzylisoquinoline Alkaloid Biosynthesis in Coptis japonica

Abstract: Selected cultured Coptis japonica cells produce a large amount of the benzylisoquinoline alkaloid berberine. Previous studies have suggested that berberine productivity is controlled at the transcript level of biosynthetic genes. We have identified a regulator of transcription in berberine biosynthesis using functional genomics with a transient RNA interference (RNAi) and overexpression of the candidate gene. The 24 primary candidate clones were selected from 1,014 expressed sequence tags (ESTs) that were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 35 publications
6
115
0
Order By: Relevance
“…The transcriptional regulation of BIA biosynthesis has recently been investigated in opium poppy (Kawano et al 2012;Mishra et al 2013), but has been more extensively studied in Coptis japonica (Kato et al 2007;Yamada et al 2011). The importance of transcriptional control in BIA metabolism is particularly evident from (1) the cell typespecific localization of biosynthetic gene transcripts (Bird et al 2003;Samanani et al 2006;Lee and Facchini 2010;Onoyovwe et al 2013) and (2) the coordinated induction of all expressed biosynthetic gene transcripts (Zulak et al 2007) and corresponding proteins (Zulak et al 2009;Desgagné-Penix et al 2010) in opium poppy cell cultures after the addition of a fungal-derived elicitor.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional regulation of BIA biosynthesis has recently been investigated in opium poppy (Kawano et al 2012;Mishra et al 2013), but has been more extensively studied in Coptis japonica (Kato et al 2007;Yamada et al 2011). The importance of transcriptional control in BIA metabolism is particularly evident from (1) the cell typespecific localization of biosynthetic gene transcripts (Bird et al 2003;Samanani et al 2006;Lee and Facchini 2010;Onoyovwe et al 2013) and (2) the coordinated induction of all expressed biosynthetic gene transcripts (Zulak et al 2007) and corresponding proteins (Zulak et al 2009;Desgagné-Penix et al 2010) in opium poppy cell cultures after the addition of a fungal-derived elicitor.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…The first transcriptional regulator of BIA metabolism was identified from C. japonica using RNAi to silence five putative regulatory factors showing reduced expression in a cultured cell line with relatively low BIA biosynthetic gene transcript levels (Kato et al 2007). The transient silencing of one candidate (CjWRKY1) resulted in a marked decrease in berberine biosynthetic gene transcripts.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…A large number of WRKY genes have been isolated and characterized in various plant species, such as in Arabidopsis (Eulgem et al, 2000), Zea mays (Wei et al, 2012), Gossypium (Dou et al, 2014), Medicago truncatula ( and Nan, 2014), Cucumis sativus (Ling et al, 2011), B. rapa , Vitis vinifera , Carica papaya (Pan and Jiang, 2014), Coffea arabica (Ramiro et al, 2010), Populus , Hevea brasiliensis , Coptis japonica (Kato et al, 2007), and Catharanthus roseus (Yang et al, 2013). However, knowledge on WRKYs of G. biloba remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al (2007) isolated and identified the transcription factor CjWRKY1 from Coptis japonica and found a positive correlation between the expression of this gene and all the examined berberine biosynthesis genes, indicating that CjWRKY1 is involved in berberine biosynthesis. Ma et al (2009) also isolated AaWRKY1 from the glandular secretory trichomes of Artemisia annua, in which artemisinin is synthesized and sequestered.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, norcoclaurine synthase (NCS), 67) columbamine O-methyltransferase (CoOMT), 68) tetrahydroberberine oxidase (THBO), 69) corytuberine synthase (CYP80G2), 70) and two transcription factors (WRKY and bHLH) were isolated and characterized. 71,72) Transient RNAi with protoplasts isolated from C. japonica cells with high berberine-productivity was highly effective in the screening genes that are difficult to isolate, and especially those for transcription factors involved in berberine biosynthesis. 71,72) When the effects of the double-stranded RNA of about 40 candidate transcription factor genes were examined, the RNAi of two genes (CjWRKY1 and CjbHLH1) showed marked reductions in the transcripts of almost all of the genes involved in berberine biosynthesis, and there was little effect on the transcript levels of glyceraldehyde-3-phosphate dehydrogenase and chorismate mutase in primary metabolism.…”
Section: )mentioning
confidence: 99%